Consider the Fibonacci polynomials

$$F_n (x) = \sum_{j = 0}^{\left\lfloor {n/2} \right\rfloor }\binom{n-j}{j} x^{n - 2j} $$
and the Lucas polynomials

$$L_n (x) = \sum_{j = 0}^{\left\lfloor {n/2} \right\rfloor }\frac{n}{n-j }\binom{n-j}{j} x^{n - 2j} .$$

Let $X$ be the multiplication operator $Xp(x)=xp(x)$ on the polynomials, $D_q$ the $q$-differentiation operator defined by $$D_q p(x)=\frac{p(qx)-p(x)}{qx-x}$$ and $A=X+(q-1)D_q$.

Applying the operator $F_n(A)$ to the constant polynomial $1$ has the curious effect that all binomial coefficients $\binom{n}{j}$ are changed to $q$-binomial coefficients ${n\brack j}$ together with some $q$-power. More specifically, we get $$F_n(A)1=F_n(x|q)= \sum_{j = 0}^{\left\lfloor {n/2} \right\rfloor } {q^{j+1\choose 2}}{n-j\brack j} x^{n - 2j} $$ and $$ L_n(A)1=L_n(x|q)= \sum_{j = 0}^{\left\lfloor {n/2} \right\rfloor } {q^{j\choose 2}}{\frac{[n]}{[n-j]}}{n-j\brack j} x^{n - 2j} .$$

Is this an isolated phenomenon or do there exist similar formulae for polynomials? In other words, are there polynomials $p_n(x)$ in one variable $x$ and operators $B(q)$ satisfying $B(1)=X$ such that $p_n(B(q))1$ is a simple or beautiful $q$-analogue of $p_n(x)$?

A trivial example would be $p_n(x)=x^n$ and $B(q)=\epsilon(q)X$ with $\epsilon(q)p(x)=p(qx)$.

**Edit**

Recently I noticed that the Rogers-Szegö polynomials $$R_n(x,s)= \sum_{j = 0}^{n }{n\brack j} x^{j}s^{n-j} $$ can also be represented in this way: $$R_n(x,s)=(x+s+(q-1)xsD_q)^n1.$$ Since this is the most natural $q-$ analogue of the binomial theorem I would be astonished if nobody has as yet seen this fact. The proof is the same as that for the well-known recursion $R_{n+1}(x,s)=xR_{n}(x,s)+(q^n-1)xs R_{n-1}(x,s).$

It follows immediately from the recurrence of the $q-$ binomial coefficients:

$(x+s+(q-1)xsD_q) \sum_{j = 0}^{n }{n\brack j} x^{j}s^{n-j}$ $=\sum_{j = 0}^{n }{n\brack j} x^{j+1}s^{n-j}$ $+\sum_{j = 0}^{n }{n\brack {j}} x^{j}s^{n-j+1}$ $+\sum_{j = 0}^{n }(q^{j}-1){n\brack j} x^{j}s^{n-j+1}$ $= \sum_{j = 0}^{n+1 }({n\brack j}+{n\brack {j-1}}+(q^{j}-1) {n\brack {j}}) x^{j} s^{n-j+1}$ $=\sum_{j = 0}^{n +1}{{n+1}\brack j} x^{j}s^{n-j+1}.$

3more comments